2017
DOI: 10.1177/2396941517722139
|View full text |Cite
|
Sign up to set email alerts
|

Do measures of memory, language, and attention predict eyewitness memory in children with and without autism?

Abstract: Background and aims: There are few investigations of the relationship between cognitive abilities (memory, language, and attention) and children's eyewitness performance in typically developing children, and even fewer in children on the autism spectrum. Such investigations are important to identify key cognitive processes underlying eyewitness recall, and assess how predictive such measures are compared to intelligence, diagnostic group status (autism or typically developing) and age. Methods: A total of 272 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…In line with previous research on both children and adults (e.g., Henry, Crane, et al, , except in the Registered Intermediary vs. best practice interview comparison; Maras & Bowler, ; Maras et al, ; Maras et al, ), we found that the memory reports of children with ASD were as complete and elaborated as that of non‐ASD children in response to both open‐ended and cued recall questioning. Additionally, children in the ASD and comparison groups did not differ with respect to the accuracy of their reports, replicating previous findings (e.g., Henry, Crane, et al, ; Henry, Messer, et al, ; Maras et al, ; Maras et al, ; Maras & Bowler, ; McCrory et al, ). However, our findings contrast with those obtained in studies that have shown episodic memory deficits in autistic children (Bruck et al, ; Henry, Messer, et al, ; Mattison et al, , ; McCrory et al, ).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…In line with previous research on both children and adults (e.g., Henry, Crane, et al, , except in the Registered Intermediary vs. best practice interview comparison; Maras & Bowler, ; Maras et al, ; Maras et al, ), we found that the memory reports of children with ASD were as complete and elaborated as that of non‐ASD children in response to both open‐ended and cued recall questioning. Additionally, children in the ASD and comparison groups did not differ with respect to the accuracy of their reports, replicating previous findings (e.g., Henry, Crane, et al, ; Henry, Messer, et al, ; Maras et al, ; Maras et al, ; Maras & Bowler, ; McCrory et al, ). However, our findings contrast with those obtained in studies that have shown episodic memory deficits in autistic children (Bruck et al, ; Henry, Messer, et al, ; Mattison et al, , ; McCrory et al, ).…”
Section: Discussionsupporting
confidence: 84%
“…However, various studies have also reported that autistic individuals can provide as much correct information about an event as TD peers, especially when appropriate support is given at retrieval (Henry, Crane, et al, ; Maras et al, ; Maras & Bowler, ). With regard to the accuracy of the information recalled soon after an event, the research findings are also not consistent, with some suggesting that individuals with ASD are less accurate than non‐ASD peers (e.g., Bruck et al, ; Maras & Bowler, , , ), whereas others have found that they are just as accurate (e.g., Henry, Crane, et al, ; Henry, Messer, et al, ; Maras et al, ; Maras et al, ; Maras & Bowler, ; McCrory et al, ). Still, other researchers have reported that specific interview techniques can help autistic children be as accurate as non‐ASD peers (Mattison et al, , ).…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations